Comparison of Tibiofemoral Joint Space Width Measurements from Standing CT and Fixed Flexion Radiography - Segal, Neil A. (J Orthop Res, 2017)
The objective of this project was to determine the relationship between medial tibiofemoral joint space width measured on fixed-flexion radiographs and the three-dimensional joint space width distribution ona low-dose, standing CT (SCT) imaging. At the 84-month visit of the Multicenter Osteoarthritis Study, 20 participants were recruited. A commercial SCT scanner for the foot and ankle was modified to image knees while standing. Medial tibiofemoral joint space width was assessed on radiographs at fixed locations from 15–30% of compartment width using validated software and on SCT by mapping the distances between three-dimensional subchondral bone surfaces. Individual joint space width values from radiographs were compared with three-dimensional joint space width values from corresponding sagittal plane locations using paired t-tests and correlation coefficients. For the 4 medial-most tibiofemoral locations, radiographic joint space width values exceeded the minimal joint space width on SCT by a mean of 2.0mm and were approximately equal to the 61st percentile value of the joint space width distribution at each respective sagittal-plane location. Correlation coefficients at these locations were 0.91–0.97 and the offsets between joint space width values from radiographs and SCT measurements were consistent. There were greater offsets and variability in the offsets between modalities closer to the tibial spine. Joint space width measurements on fixed-flexion radiographs are highly correlated with three-dimensional joint space width from SCT. In addition to avoiding bony overlap obscuring the joint, a limitation of radiographs, the current study supports a role for SCT in the evaluation of tibiofemoral OA.